THE IMPACT OF MOTHER-TODDLER CLASSES ON STUNTING PREVENTION PRACTICES AMONG MOTHERS OF YOUNG CHILDREN - Umriaty Umriaty; Evi Zulfiana (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
The prevalence of stunting according to WHO in 2021 is 22%. In Indonesia, according to SSGI data in 2022, the stunting rate in 2021 was 24.4%, down 2.8% to 21.6%. Central Java Province in 2022 by 20.8%. This study aims to determine the influence of the class of mothers under five on maternal knowledge and preventive behavior about stunting. This research was conducted at the UPTD Sumurpanggang Health Center in Tegal City in June 2024 with the Case Control research method. The dependent variables in this study are maternal knowledge and preventive behavior against stunting. The independent variable in this study was the class of mothers under five. The population in this study was mothers of toddlers aged 12-24 months. The sample used in this study was a number of mothers who attended toddler classes three times as the case group and those who did not attend toddler classes as the control group. The sampling technique used was purposive sampling. Univariate data analysis in this study used frequency distribution and bivariate analysis using Chi Square. The results showed that there was no significant relationship between participation in toddler mother classes and knowledge about stunting, feeding behavior, and supportive behavior for the prevention of stunting.